Response to effects of reactiv "maximum beta-hydroxy beta-methylbutyrate" on body mass and performance in elite male rugby players - McIntosh, N. D.; Love, T. D.; Haszard, J.; Osborne, H.; Black, K. E. (The Journal of Strength and Conditioning Research, 2018)
Request for Clarification: